Comparison of lower limb strength characteristics between youth and adult elite female team handball players - Ravier, G.; Demouge, J. (Science & Sports, 2016)
Objectives: To analyse isometric strength and power-force-velocity profiling in youth and adult elite female handball players and to determine the differences in these capabilities according to age, anthropometric characteristics and playing positions. Methods: Twenty-one youths and 18 adults were tested in dynamic and isometric conditions. Power-load profiling was assessed from leg press using loads ranging from 30 to 90% of one maximum repetition. The maximal voluntary contraction and the rate of force development (times intervals 50-200 ms) were analysed during isometric knee extension. Results: A markedly difference was observed between youth and adult groups for their mechanical capabilities. Specifically the adult group's values were much higher than those of the youth players for power output at all loads tested (P < 0.05 to P < 0.0001) and for the rate of force development (P < 0.05 to P < 0.01). When considering playing positions, the comparison between youth and adult players revealed higher power output for wing and backcourt adult players. However, any difference was detected between playing positions neither within youth nor within adult players. The anthropometric data revealed lower height for youth backcourt compared with adult backcourt players. Surprisingly, no difference was found between adults and youths for body mass values. Backcourt players were heavier and taller compared with wings within adults and youths. This result suggested that anthropometric characteristics were related to playing positions. Conclusions: These results provide novel data on the strength characteristics that distinguished youth and adult players. Increasing power output and explosive force should be prescribed to young players hoping to reach a top-class performance level.